Critical Security Perspectives on the U.S.-Mexico Border - Çağla Lüleci-sula (Siyasal: Journal of Political Sciences)
Critical approaches to security have enriched the literature significantly by provoking novel theoretical debates and introducing new areas of research since their entrance into the field. They have deepened and widened the traditional understanding of security by introducing referent objects other than the state and types of threats other than the military. These attempts have distracted security studies’ extensive focus on state security and pointed to new research topics that were traditionally excluded from the scope of security studies. Curious about how different critical security approaches make sense of the migration-security nexus, this study examines how the Copenhagen School (discursive approach) and the Paris School (sociological approach) analyze the U.S.-Mexico border. It first examines how these two schools of thought define, understand, and approach security. Second, it directs its focus on the critical security literature on the U.S.-Mexico borderland. Third, the article discusses both approaches’ accounts on the same border and how they handle dis/similar aspects of the migration-security nexus. The study concludes by defending the argument that bridging these two critical security approaches may increase their analytical power in making sense of the migration-security nexus.